Awareness, screening, Practices and attitudes of cervical cancer among doctors and nursing staff working at a tertiary care center - Erum Majid; Majid Ahmed Shaikh; Osama Ahmed Qazi; Saba Khan; Irfan Majeed; Khadija Bano (Journal of the Pakistan Medical Association, 2022)
Objectives: To assess knowledge, attitude and practice of medical and paramedical staff about cervical cancer as well as its screening and prevention. Methods: The descriptive cross-sectional study was conducted at the Jinnah Post-graduate Medical Centre, Karachi, from March 1 to August 30, 2019, and comprised women medical and paramedical staff randomly selected from different specialties. Data was collected using a structured questionnaire. Data was analysed using SPSS 20. Results: Of the 347 participants 144(41.5%) were nurses and 203(58.5%) were doctors. The overall mean age was 26.22±6.38 years. Of the total, 108(30%) respondents were married and 239(68%) were single. Overall, 239(68.8%) were well aware of Pap smear being the screening test; 85(24.5%) were aware of the true guidelines to repeat the test; 152(43.8%) had an idea of the exact use of visual Inspection with acetic acid; 61(17.6%) had got a Pap smear done; and 156(45%) thought they were at risk of developing carcinoma cervix. The common risk factors identified were multiple sexual partners 254(73.2%), age at first sexual intercourse 160(46%), smoking 131(37.8%), foul-smelling discharge 221(63.7%), and post-coital bleeding 231(66.6%). Conclusion: Cervical cancer prevalence is rising due to inadequate knowledge and awareness among healthcare personals. Improvement can be brought by regular use of Pap smear. Key Words: Cervical cancer, Pap smear, Healthcare professionals, Visual inspection with acetic acid.